Effect of Islamic Spiritual Mindfulness via Mobile Aplication (SI-DEPAPU) on Social Interaction in Isolated Patients - Vivi Sovianti; Meidiana Dwidiyanti; Suhartini Ismail (JKG (JURNAL KEPERAWATAN GLOBAL), 2025)
Background: Social interaction is an important indicator during the process of social isolation treatment. The less active social interaction could lead to other mental disorders such as hallucination, suicide risk, self-care deficit, and violence risk. The study investigated the effect of Islamic Spiritual Mindfulness on Discharged Patient Detection Information System (SI-DEPAPU) application to enhance the social interaction of schizophrenia patients with social isolation. Methods: The research design used was quasi-experimental with a pre-post test method. The study used purposive sampling with 40 respondents divided into two groups of 20 people each. The instruments used were the Social Interaction Questionnaire and Behavioral Observation Sheet, which have been tested for validity and reliability. The statistical tests used included the paired t-test to assess social interaction within the group, the independent t-test to compare before the intervention, and the Mann-Whitney test for after the intervention. Results: The research finding showed the difference in the social interaction of patients before and after the intervention between the intervention group and control group (p=<0.001; <0.05), of which the mean value of the intervention group (43.79) was more significant than the control group (15.21). Conclusion: Based on the research results, it can be concluded that there was an increase in social interaction in patients after receiving Islamic spiritual mindfulness therapy. The SI-DEPAPU application can be implemented as a mental health nursing intervention to improve the social interaction of patients with schizophrenia who suffer from social isolation.